Rythu Bharosa Kendram: Rejuvenating the Indian Rural Economy - Shaik Reshma Sulthana; Dobbali Srujan; Remalli Anthony; Meda Himabindu; Doke Vipul Yuvraj (Archives of Current Research International, 2024)
Rythu Bharosa Kendram (RBK) serves as one stop shop for all of the needs of farmers at the Panchayat level. They offer services like e-crop booking for crop insurance, an agricultural input store, farmer knowledge centers, a technical advisory team, YSR Rythu Bharosa, Polambadi (Farmer Field School), CCRC cards, D-Krishi Seed distribution, and others. The objective is to study the extent of adoption of technologies and services of RBKs by the farmers. The present study is conducted in Prakasam district of Andhra Pradesh state as it is has significant area under crop cultivation. Multi stage simple random sampling technique has been adopted to select the sample farmers for the study. The data was collected from 75 respondents by personal interview method and analyzed using statistical analytical techniques such as Mean scale value and adoption Index. The study revealed that the majority of respondents 58.67% adopted technology at a medium level followed by low adoption 26.67% and high adoption 14.67% levels. The study concludes that RBKs are vital in serving farmers, with moderate adoption levels influenced by farmers’ age and education.